Examining teacher assessment literacy and assessment efficacy: an exploratory study. - Ong , Saw Lan

(untitled)
This study attempts to examine the gap between teachers' assessment literacy and assessment practices through the development of the teacher assessment literacy model (LPG Model) and teacher assessment practices model (APG Model). The equivalence of the model was also examined for teachers with different years of teaching experience, subject area and school level.